2020
DOI: 10.1002/jbmr.4430
|View full text |Cite
|
Sign up to set email alerts
|

gp130 Cytokines Activate Novel Signaling Pathways and Alter Bone Dissemination in ER+ Breast Cancer Cells

Abstract: Breast cancer cells frequently home to the bone marrow, where they encounter signals that promote survival and quiescence or stimulate their proliferation. The interleukin‐6 (IL‐6) cytokines signal through the co‐receptor glycoprotein130 (gp130) and are abundantly secreted within the bone microenvironment. Breast cancer cell expression of leukemia inhibitory factor (LIF) receptor (LIFR)/STAT3 signaling promotes tumor dormancy in the bone, but it is unclear which, if any of the cytokines that signal through LIF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 70 publications
0
6
0
Order By: Relevance
“…Several studies have reported growth-inhibitory effects of OSM in BC cell line models [196,[202][203][204][205], as well as in normal human mammary epithelial cells [206]. Conversely, cell line studies have also suggested that OSM might exert a pro-tumorigenic and prometastatic effect through induction of detachment, invasiveness, bone dissemination and EMT [160,[207][208][209]. Studies in animal models showed that OSM knockdown reduced the formation of metastases, with findings suggesting that autocrine and paracrine signalling might be linked to metastasis to bone and lungs, respectively [210,211].…”
Section: Osmmentioning
confidence: 99%
“…Several studies have reported growth-inhibitory effects of OSM in BC cell line models [196,[202][203][204][205], as well as in normal human mammary epithelial cells [206]. Conversely, cell line studies have also suggested that OSM might exert a pro-tumorigenic and prometastatic effect through induction of detachment, invasiveness, bone dissemination and EMT [160,[207][208][209]. Studies in animal models showed that OSM knockdown reduced the formation of metastases, with findings suggesting that autocrine and paracrine signalling might be linked to metastasis to bone and lungs, respectively [210,211].…”
Section: Osmmentioning
confidence: 99%
“…No formal assessment of osteoclast numbers in vivo was made, but the authors showed that OSM enhanced osteoclast formation in RANKL-stimulated cocultures of breast cancer cells and the pro-osteoclastic cell line RAW264.7, an effect that was mediated by OSMR on breast cancer cells and decreased expression of OPG. In line with these studies, it has recently been reported that OSM may play a stimulatory role in bone metastases of ER + (estrogen receptor positive) breast cancer cells in which the OSMR is more highly expressed compared to the less aggressive ER − cells [ 145 ]. In inflammatory diseases, OSM is proposed to function as a stimulator of osteoclast formation and bone loss, whereas OSM is suggested to be a stimulator of bone formation in heterotopic ossification.…”
Section: Discussionmentioning
confidence: 89%
“…This effect was further elevated when the PTHrP NLS and C-terminal domain were deleted. LIFR is known to activate STAT3, ERK, and AKT signaling, among numerous other signaling pathways in breast cancer [ 32 , 42 , 56 ]. It has been postulated that LIFR signaling promotes tumor dormancy specifically through STAT3 activation [ 32 ]; however, the oncogenic ERK and AKT pathways can still be activated by LIFR-binding cytokines [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…LIFR is known to activate STAT3, ERK, and AKT signaling, among numerous other signaling pathways in breast cancer [ 32 , 42 , 56 ]. It has been postulated that LIFR signaling promotes tumor dormancy specifically through STAT3 activation [ 32 ]; however, the oncogenic ERK and AKT pathways can still be activated by LIFR-binding cytokines [ 42 ]. Our data here suggest that the EC359 LIFR inhibitor may preferentially decrease LIFR-mediated ERK signaling, shifting the balance towards p38 activity and suppression of cell proliferation in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation